Leiomiossarcoma gástrico associado a hérnia de hiato em cão da raça Shar-pei: Relato de caso - Prado, L. O C [UNESP]; Franco, G. G. [UNESP]; Legatti, E. [UNESP]; Ranzani, J. J T [UNESP]; Quitzan, J. G. [UNESP]; Siqueira, E. G M [UNESP]; Souza, J. A L [UNESP]; Minto, B. W. [UNESP]; Brandão, C. V S [UNESP] (FapUNIFESP (SciELO), 2017)
Gastrointestinal system tumors are not common in Veterinary Medicine and stomach neoplasia represents less than 1% of all malignant tumors. Among digestive neoplasias, the leiomyosarcoma is the second most common with predisposition to the regions of the jejunum and cecum, but any portion from the esophagus to rectum can be potentially affected. This is a case report of a 13-year-old male Shar-pei dog with medical history of post prandial emetic episodes and progressive weight loss lasting eight months. Surgical intervention was indicated after radiographs and endoscopic evaluation, where a gastric mass and hiatal hernia were found. The diagnosis of gastric leiomyosarcoma was established only after histopathological analysis. Despite the patient having little survival time, this clinical presentation of a gastric tumor associated with hiatal hernia is rare, and exalts the importance of histopathological studies as a tool for the correct diagnosis in these unusual diseases.
Gastric leiomyosarcoma associated with hiatal hernia in a Shar-pei: A case report
Keywords: Oncology; Stomach; Surgery; Tumor